Current Trends in the Monitoring and Treatment of Diabetic Retinopathy in Young Adults - Dorota Raczyńska; Katarzyna Zorena; Beata Urban; Dominik Zalewski; Andrzej Skorek; Grażyna Malukiewicz; Bartosz L. Sikorski (Hindawi Limited, 2014)
The diagnosis and treatment of diabetic retinopathy (DR) in young adults have significantly improved in recent years. Research methods have widened significantly, for example, by introducing spectral optical tomography of the eye. Invasive diagnostics, for example, fluorescein angiography, are done less frequently. The early introduction of an insulin pump to improve the administration of insulin is likely to delay the development of diabetic retinopathy, which is particularly important for young patients with type 1 diabetes mellitus (T1DM). The first years of diabetes occurring during childhood and youth are the most appropriate to introduce proper therapeutic intervention before any irreversible changes in the eyes appear. The treatment of DR includes increased metabolic control, laserotherapy, pharmacological treatment (antiangiogenic and anti-inflammatory treatment, enzymatic vitreolysis, and intravitreal injections), and surgery. This paper summarizes the up-to-date developments in the diagnostics and treatment of DR. In the literature search, authors used online databases, PubMed, and clinitrials.gov and browsed through individual ophthalmology journals, books, and leading pharmaceutical company websites.